Folk name and lore of birds from the Sundanese of West Java, Indonesia: An ethno-ornithological survey - DEDE MULYANTO; JOHAN ISKANDAR; ALIYA MADANI; RIMBO GUNAWAN; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Mulyanto D, Iskandar J, Madani A, Gunawan R, Partasasmita R. 2020. Folk name and lore of birds from the Sundanese of West Java, Indonesia: An ethno-ornithological survey. Biodiversitas 21: 4384-4395. Since last time, research on birds in West Java had been undertaken by ornithologists. The ethnoornithology research, however, has been rarely employed. The study aims were to account for vernacular or folk names, folk classification, and folkloric birds based on case of the mountain people of Keratasari, West Java, Indonesia. The method in this study was qualitative with the ethnoornithological approach. The field data were collected by focus group discussion and deep interviews with informants of 12 groups of independent village people of four villages of Kertasari sub-district. The naming of collected data was by systematic elicitation of names from pictorial representations of birds and organized here to facilitate analysis of various aspects of folk taxonomy about the scientific one. Folklore about birds that were collected in natural contexts is also included to indicate the birds' role and their names in symbolic processes that exceed the limits of literal reference. The result of the study showed that it was recorded 222 bird species, representing 170 vernacular names, 93 of them were recorded by Koningsberger (1901-1909). The taxonomic and folkloric mode of knowledge in this paper presents that birds play important roles in villagers' lives of Sundanese people, particularly in the study area. Generally, birds have been an important role in socio-cultural aspects, including in folklore of Sundanese people who reside in rural mountain areas of West Java.